2016
DOI: 10.1002/ett.3014
|View full text |Cite
|
Sign up to set email alerts
|

Power efficient CoMP‐joint transmission with two stage QoSs

Abstract: Power efficiency has become an important design goal for wireless communications, and a coordinated multi-point (CoMP) with joint transmission (JT) scheme can be implemented to improve the cell edge throughput by increasing the signal-to-interference ratio, which in turn leads to power savings through cooperative transmission. To this end, we propose a power control scheme in which the cooperating base station can reduce its own transmission power while remaining within two stage quality of service (QoS) const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…(ii) SecondNear-CoMP [16]: We assume that system bandwidth is shared by all the SUEs, and SUEs are associated with the nearest SBS and the SBS (except the serving SBS) nearest to the SUE from the set of SBSs which has not been chosen by other SUEs as their coordinated multipoint joint transmission (CoMP-JT) SBSs. Moreover, Algorithm 2 is adopted as the power allocation optimization algorithm.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) SecondNear-CoMP [16]: We assume that system bandwidth is shared by all the SUEs, and SUEs are associated with the nearest SBS and the SBS (except the serving SBS) nearest to the SUE from the set of SBSs which has not been chosen by other SUEs as their coordinated multipoint joint transmission (CoMP-JT) SBSs. Moreover, Algorithm 2 is adopted as the power allocation optimization algorithm.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Its element is an association indicator decision variable ∈ {0, 1} denoting whether SBS is associated with SUE , = 1, if SBS is associated with SUE ; otherwise = 0. From [16], we can derive the received signal strength of SUE associated with one or more SBSs as follows:…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
“…23,24 In Abdelkefi et al, 25 the performance of CoMP technique is studied with CSI error and it is shown that error in estimating CSI can significantly influence the performance. [27][28][29][30][31] Both CR and CoMP transmission are highly promising paradigms for future cellular networks. However, all these issues can be solved with some extra efforts.…”
Section: Discussionmentioning
confidence: 99%
“…21 In this research, we consider CoMP JT technique, which has received significant attention from the wireless communication research community. [27][28][29][30][31] Both CR and CoMP transmission are highly promising paradigms for future cellular networks. Several researches have been conducted on CoMP transmission-based CRNs.…”
Section: Discussionmentioning
confidence: 99%
“…, (10) where x > 0, 𝜖 > 0 is the mean, 𝛿 > 0 is the shape parameter and, 𝜙(.) is the CDF of the standard normal distribution.…”
Section: Effective Channel Gain Modelingmentioning
confidence: 99%